Managing Conflict of Interest: Shifting between political PR and journalism. (2nd April 2016) - Fisher, Caroline
Abstract : When a journalist returns to political reporting after working as a political media adviser it can trigger concern about conflict of interest based on a suspicion of partisanship. Despite this, there is little discussion in the journalism literature about how reporters should manage this type of conflict when it arises. This paper reports on a selection of findings from wider inductive, qualitative research into the career transition from journalism to political media advising and back again. Semi-structured, in-depth interviews conducted with 21 journalists who had moved between the two roles revealed that the media advisers took four main routes back to journalism in an attempt to manage the possible conflicts: "Escape"; Being "laundered"; Going "straight back in"; and "Cooling-off". Based on these findings, this paper argues that a uniform approach to managing the transition from political advising to journalism could be useful in easing public concern about conflicts of interest.